On Modeling and Developing Self-Healing Web Services Using Aspects - Mostefaoui, Ghita Kouadri; Maamar, Zakaria; Narendra, Nanjangud C; Thiran, Philippe (2007 2nd International Conference on Communication Systems Software & Middleware : Bangalore, India, 7-12 January 2007, 2007)
Like any computing application, Web services are subject to failure and unavailability due to multiple reasons like Web service faulty-code and unreliable communication-infrastructure. A manual correction of Web services failure is error-prone and time-consuming. An effective Web services environment should be able to monitor its state, diagnosis faults, and automatically recover from failures. This process is known as self-healing. In this paper, we address self-healing issues of Web services using Aspect-Oriented Programming (AOP). AOP supports separation of self-healing concerns from Web services code and promotes maintenance and reusability.